The Effect of Teachers’ Attitudes and Teacher Efficacy for Inclusive Education on Emotional Distress in Primary School Teachers in Japan - Nagase, Kai; Tsunoda, Kenji; Fujita, Kumi (Frontiers in Education, 2020)
The purpose of this study is to examine the relationship between teachers’ attitudes toward and teacher efficacy in inclusive education, and the emotional distress in Japan. A survey of 158 primary school teachers in Yamaguchi prefecture, Japan measured the attitudes of regular and special education teachers for inclusive education and teacher efficacy toward inclusive education to assess the impact of these factors on teachers’ emotional distress. The results indicated that the teachers’ emotional distress was significantly and negatively correlated with attitudes toward integrated classroom management and perceived ability to teach students with disabilities. Furthermore, teachers’ emotional distress was significantly and negatively correlated with high teacher efficacy in inclusive instruction, collaboration, and managing behavior. A regression analysis was performed which further confirmed that efficacy in collaboration and managing behavior were unique predictors of emotional distress in primary school teachers. These findings can provide useful insights into the issue of emotional distress in primary school teachers.